PERAN GURU DALAM PROMOSI KESEHATAN GIGI DAN MULUT DI SEKOLAH - Hermien Nugraheni; Lanny Sunarjo; Tri Wiyatini (Jurnal Kesehatan Gigi, 2018)
TITLETEACHER’S ROLE ON ORAL HEALTH PROMOTING SCHOOLABSTRACTChildren's dental and oral health is generally found to be in poor condition with the presence of plaques and other deposits on the surface of the teeth. Behavior that tends to ignore dental and oral hygiene is generally based on a lack of knowledge about dental and oral health and its maintenance. School student intervention is carried out with the aim that learning about hygiene and dental health can be carried out as early as possible to increase students' knowledge about the importance of maintaining health, especially dental and oral health. The teacher component is the best promoter in educational activities because they are familiar with the method of educating and motivating school students. This study aims to determine the role of teachers in efforts to promote dental and oral health in students at school.This research’s design is descriptive with a qualitative approach. Informants in this study were selected through a purposive sampling technique. The main informants in this study amounted to 3 people, consisting of UKS / UKGS Mentors teachers, while the triangulation informants in this study were 2 people, consisting of the vice principal and the UKS / UKGS supervisor from the Puskesmas.The results of the study indicate that UKGS activities, as a forum for promotion of dental and oral health of students in schools, are recommended for routine training for teachers to improve their knowledge and attitudes so that they can motivate teachers to actively take the initiative to develop various activities related to oral health promotion at school.